VD_FINDINFO Pron / 2013 / 57 vom 4. März 2013 - VD Tribunal cantonal (2013)
ACTE DE L'ÉTAT CIVIL, ÉTAT CIVIL, FRAIS JUDICIAIRES, JUGE DE PAIX, SUCCESSION | 110 CPC (CH), 322 al. 1 CPC (CH), 322 CPC (CH)